Pemanfaatan Media Sosial Sebagai Media Pemasaran dalam Meningkatakan Perekonomian di Sektor Budidaya Ikan Desa Canggu - Rahmawati, Sofiyah; Wahyuni, Anik; Mustofa, Misbahul (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
This study aims to provide education through counseling regarding the use of social media to increase promotion and marketing in the fish farming sector in Canggu Village. The instrument used in this study was an interview guide that was conducted to counseling participants. The implementation of this research consisted of three stages, namely the first stage, namely interviews, the second stage of socialization, and the third stage, namely providing solutions in the form of counseling regarding the use of social media as a marketing medium to improve the economy in the fish farming sector. Counseling on marketing using social media to improve the economy in the field of fish farming in Canggu Village is expected to increase sales of fish farming and optimize marketing using online social media.